A high-bonding lithium-ion battery separator and preparation method thereof
By using PVDF powder, wrinkled MoS2@KHCO3 nanosheets and modified polyethyleneimine in lithium-ion battery separators, the shortcomings of existing separators in the electrode sheet bonding performance, electrolyte affinity and flame retardant performance are solved. , achieves a high viscosity and high flame retardant diaphragm, improving the overall performance of the battery.
Patent Information
- Application Number
- CN202211099998.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-09-07
AI Technical Summary
The existing lithium-ion battery separators have shortcomings in the adhesive properties of the electrode sheet, electrolyte affinity and flame retardant properties, resulting in limited improvement in battery energy density, low mechanical strength and easy to cause heat loss.
PVDF powder and wrinkled MoS2@KHCO3 nanosheets are used as the main components of the separator, and a highly adhesive and flame retardant separator is formed by modifying polyethyleneimine as the binder.
The mechanical strength, flame retardant and electrolyte properties of the separator are significantly improved, the adhesion of the electrode sheet and the wetting properties of the electrolyte are enhanced, and the heat resistance of the separator and the cycle stability of the battery are improved.
Smart Images

Figure BDA0003836809210000141 
Figure BDA0003836809210000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery separators, in particular to a high-adhesion lithium-ion battery separator and a preparation method thereof. Background Art
[0002] In recent years, with the increasing demand for new energy vehicles in the automotive market, the market demand for lithium-ion batteries, one of the core components of electric vehicles, has also increased. Lithium-ion batteries are mainly composed of diaphragms, electrolytes, positive electrode materials, and negative electrode materials. The charging and discharging process of the battery is completed by the movement of lithium ions back and forth between the positive and negative electrodes through the electrolyte. The diaphragm prevents the positive and negative electrodes from contacting but allows lithium ions to pass through. Therefore, the performance of the diaphragm directly affects the various performances of the battery and the safety of battery use.
[0003] At present, the commonly used separators for lithium-ion batteries are polyolefin separators such as PP and PE. Although they have advantages such as good mechanical properties, good electrochemical properties and moderate prices, they also have some disadvantages: ① Poor adhesion to the pole piece and insufficient affinity for the electrolyte, which limits the improvement of the battery energy density; ② Low mechanical strength and poor puncture resistance, which are prone to thermal runaway; ③ Low melting point, the separator is prone to rupture during thermal runaway, causing battery combustion and explosion. At present, most of the existing polyolefin separators are coated with a water-based PVDF adhesive layer to improve the poor adhesion of the existing polyolefin separator to the pole piece and the poor wettability of the electrolyte, but PVDF has a high degree of crystallinity and interface resistance, which makes it have poor affinity for the embedded liquid electrolyte. Summary of the invention
[0004] The object of the present invention is to provide a highly adhesive lithium ion battery separator and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A high-bonding lithium-ion battery separator comprises a base film and a coating layer. The raw material composition of the coating layer is, by mass percentage, 8.5%-18.5% of wrinkled MoS2@KHCO3 nanosheets, 0-1.6% of a dispersant, 20%-25% of PVDF powder, 7%-10% of a thickener, 2%-4% of an adhesive, 0.2%-0.5% of a wetting agent, 0.05%-0.2% of a defoaming agent, and the balance is ultrapure water.
[0007] Furthermore, the dispersant is an aliphatic amide dispersant, the thickener is sodium hydroxymethyl cellulose, the wetting agent is an alkyl sulfate wetting agent, and the defoaming agent is a polyether defoaming agent.
[0008] Furthermore, the preparation of wrinkled MoS2@KHCO3 nanosheets includes the following steps:
[0009] The wrinkled MoS2 nanosheets and ultrapure water were mixed and stirred for 3-4 hours, ultrasonically dispersed for 5-6 hours, potassium carbonate was added and stirred to dissolve, and then a mixed gas of carbon dioxide and nitrogen was introduced for 150-170 minutes, filtered and washed, and placed in a vacuum dryer at 70-80°C for 22-24 hours to obtain wrinkled MoS2@KHCO3 nanosheets.
[0010] Furthermore, the volume ratio of carbon dioxide to nitrogen in the mixed gas is 67.5:32.5, and the vacuum degree of vacuum drying is 0.08 MPa.
[0011] Further, the preparation of wrinkled MoS2 nanosheets includes the following steps:
[0012] Sodium molybdate dihydrate and ultrapure water are mixed, and ultrasonic treatment is performed for 8-10 minutes. L-cysteine is added and ultrasonic treatment is performed for 8-10 minutes to obtain a sodium molybdate mixed solution, which is then transferred to a stainless steel autoclave with a PTFE liner and kept at 215-220°C for 22-24 hours; the solution is naturally cooled, centrifuged, and washed alternately with deionized water and anhydrous ethanol for 3-5 times; after drying, the obtained powder is mixed with 80% hydrazine hydrate at a mass volume ratio of 1g:20mL, and the solution is transferred to a stainless steel autoclave with a PTFE liner, and kept at 90-95°C for 4-5 hours; the solution is naturally cooled, filtered, and washed alternately with deionized water and anhydrous ethanol for 3-5 times; and annealed to obtain wrinkled MoS2 nanosheets.
[0013] Furthermore, the composition of the sodium molybdate mixed solution is: ultrapure water as solvent, wherein dihydrate sodium molybdate is 0.06 mol / L, and L-cysteine is 0.46 mol / L; the working conditions of the annealing treatment are: annealing temperature is 800° C., and annealing time is 2 h.
[0014] Furthermore, the binder is modified polyethyleneimine, and the preparation comprises the following steps:
[0015] The branched polyethyleneimine and NaOH solution are mixed and stirred, epichlorohydrin is added, and the mixture is kept warm at 3-4°C for 15-20 minutes; β-cyclodextrin and ultrapure water are added, and the mixture is kept warm in a water bath at 55-60°C for 2 hours; terephthalaldehyde and methanol are added, and the mixture is stirred for 40-60 minutes; p-formylbenzoic acid is added, and the mixture is stirred for 20-30 minutes; and the mixture is vacuum dried at 50-60°C for 11-12 hours to obtain modified polyethyleneimine.
[0016] Furthermore, the volume mass ratio of branched polyethyleneimine, epichlorohydrin, β-cyclodextrin, terephthalaldehyde, and p-formylbenzoic acid is 1 mL: 100 μL: 0.567 g: 0.02 g: 0.025 g.
[0017] Furthermore, a method for preparing a highly bonded lithium-ion battery separator comprises the following steps:
[0018] S1: Preparation of wrinkled MoS2 nanosheets;
[0019] S2: Preparation of wrinkled MoS2@KHCO3 nanosheets using wrinkled MoS2 nanosheets;
[0020] S3: Mix the dispersant, PVDF powder, wrinkled MoS2@KHCO3 nanosheets and ultrapure water for 10-30 minutes at a speed of 200-250rpm; add the thickener and continue stirring for 40-50 minutes at a speed of 400-500rpm; add the adhesive and stir for 40-60 minutes at a speed of 500-600rpm; add the wetting agent and defoaming agent and stir for 30-50 minutes at a speed of 550-600rpm; filter and remove iron to obtain a coating slurry;
[0021] S4: The prepared coating slurry is roll-coated on both sides of the polyolefin separator in steps by using a micro-gravure roller coating process, baked at 65-75°C, and rolled up to obtain a highly adhesive lithium-ion battery separator.
[0022] Furthermore, the PVDF powder is a modified PVDF powder, and the preparation thereof comprises the following steps:
[0023] 1) Wash the ion exchange resin with deionized water until it is neutral, and then put it into a chromatography column; dilute the [EMIM]Br concentration to 0.05 mol / L with deionized water, put it into the chromatography column and let it stand for 1-2 hours, dripping at a rate of 50 seconds per drop. After the exchange is complete, neutralize it with 3-mercaptopropionic acid to a pH of 5.4, and rotary evaporate to obtain an ionic liquid;
[0024] 2) 1H-pyrrole-2,5-dicarboxylic acid, sodium hydroxide and ultrapure water are mixed, ultrasonically stirred, aluminum chloride hexahydrate is added, stirred for 20-30 minutes, heated to 100° C. and stirred for 11-12 hours, filtered and washed with water and ethanol for 3-5 times in sequence to obtain an aluminum-based organic framework;
[0025] 3) Lithium bis(trifluoromethanesulfonyl)imide and ionic liquid are mixed and stirred, kept at 90-100° C. for 11-12 hours, an aluminum-based organic framework is added and ground, and then vacuum dried at 90-100° C. for 11-12 hours to obtain modified lithium ion powder; the modified lithium ion powder and N,N-dimethylformamide are mixed and stirred, PVDF powder is added and continued to be stirred, and the modified PVDF powder is ground after drying to obtain modified PVDF powder.
[0026] Furthermore, the mass ratio of the modified lithium ion powder to the PVDF powder is 10%-20%.
[0027] Beneficial effects of the present invention:
[0028] The present invention provides a high-adhesion lithium-ion battery separator and a preparation method thereof. PVDF powder and wrinkled MoS2@KHCO3 nanosheets are selected to prepare the separator. The obtained lithium-ion battery separator has high flame retardancy, high adhesion and good electrophilic electrolyte performance.
[0029] The introduction of wrinkled MoS2@KHCO3 nanosheets, thanks to its own excellent performance, greatly improves the mechanical strength of the diaphragm; the wrinkled MoS2 nanosheets have good high temperature resistance and thermal conductivity, which is conducive to improving the heat resistance of the coating, thereby improving the heat resistance of the diaphragm, and the wrinkled MoS2 nanosheets, PVDF and KHCO3 with flame retardant properties work synergistically, which further improves the heat resistance of the diaphragm;
[0030] The introduction of wrinkled MoS2@KHCO3 nanosheets also greatly improves the flame retardancy of the diaphragm, because when the temperature rises to the decomposition temperature of KHCO3, it will decompose and release water vapor and carbon dioxide, absorb latent heat, reduce the concentration of oxygen and combustible gas near the surface of the burning object, inhibit surface combustion, and the protective layer formed on the surface prevents the entry of oxygen and heat. At the same time, the potassium carbonate generated by its decomposition has good high temperature resistance, which can improve the ability of the diaphragm to resist open flames.
[0031] Thanks to the wrinkled structure on the surface of MoS2@KHCO3 nanosheets, PVDF powder adheres to the surface of MoS2@KHCO3 nanosheets more firmly, which greatly improves the adhesion of the diaphragm to the electrode and the wettability of the electrolyte, and also greatly improves the problem of powder shedding of the PVDF coating.
[0032] The present invention adopts modified polyethyleneimine as a binder to increase the ion loading capacity of the diaphragm; firstly, β-dextrin is chemically cross-linked with branched polyethyleneimine to form a prepolymer, and then terephthalaldehyde and p-formylbenzoic acid are used to continue cross-linking to prepare a self-healing binder with a network structure, and the self-healing property of the binder is used to improve the stability of the microstructure of the diaphragm, and the reversible destruction and formation of chemical bonds are used to repair the structural damage caused by the volume change of the diaphragm, and to enhance the mechanical strength of the diaphragm, thereby facilitating the improvement of the battery's specific capacity and cycle stability and other characteristics; the carboxyl groups in the self-healing binder can combine with lithium ions to provide a migration path for lithium ions, thereby greatly improving the ion exchange capacity of the diaphragm.
[0033] In order to make the adhesion of PVDF powder to MoS2@KHCO3 nanosheets durable, the present invention modifies the PVDF powder so that the PVDF powder is uniformly and firmly adhered to the MoS2@KHCO3 nanosheets without adding a dispersant, and the addition of the modified PVDF powder greatly improves the ionic conductivity and flame retardancy of the diaphragm.
[0034] First, functionalized lithium ion liquid containing thiol groups and aluminum-based organic frameworks are prepared, and then a simple and green hydrothermal method is used to synthesize an aluminum-based organic framework material with a highly stable three-dimensional structure. The high porosity and high adsorption of the aluminum-based organic framework are used to enclose the lithium ion liquid to form an ion conductor. The adsorption of the lithium ion liquid will not affect the performance of the aluminum-based organic framework, thereby modifying the PVDF powder to synergistically improve the ionic conductivity, flame retardancy and high temperature resistance of the diaphragm. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, back, etc., the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0037] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0038] Example 1
[0039] A method for preparing a highly bonded lithium-ion battery separator comprises the following steps:
[0040] S1: Preparation of wrinkled MoS2 nanosheets:
[0041] Sodium molybdate dihydrate and ultrapure water were mixed, ultrasonically treated for 8 minutes, L-cysteine was added and ultrasonically treated for 8 minutes to obtain a sodium molybdate mixed solution, which was transferred to a stainless steel autoclave with a PTFE liner and kept at 215°C for 24 hours; naturally cooled, centrifuged, and washed alternately with deionized water and anhydrous ethanol for 3 times; after drying, the obtained powder was mixed with hydrazine hydrate with a mass fraction of 80% at a mass volume ratio of 1g:20mL, transferred to a stainless steel autoclave with a PTFE liner, kept at 90°C for 5 hours, naturally cooled, filtered, and washed alternately with deionized water and anhydrous ethanol for 3 times, annealed to obtain wrinkled MoS2 nanosheets;
[0042] The composition of the sodium molybdate mixed solution is: ultrapure water as solvent, wherein dihydrate sodium molybdate is 0.06 mol / L, and L-cysteine is 0.46 mol / L; the working conditions of the annealing treatment are: annealing temperature is 800°C, and annealing time is 2h;
[0043] S2: Preparation of wrinkled MoS2@KHCO3 nanosheets using wrinkled MoS2 nanosheets:
[0044] 1.33 g of wrinkled MoS2 nanosheets and 100 mL of ultrapure water were mixed and stirred for 3 h, ultrasonically dispersed for 5 h, 115 g of potassium carbonate was added and stirred to dissolve, and then a mixed gas of carbon dioxide and nitrogen was introduced for 150 min, filtered, washed, and placed in a vacuum dryer at 70 ° C for 24 h to obtain wrinkled MoS2@KHCO3 nanosheets;
[0045] The volume ratio of carbon dioxide to nitrogen in the mixed gas is 67.5:32.5, and the vacuum degree of vacuum drying is 0.08Mpa;
[0046] S3: Mix the dispersant, PVDF powder, wrinkled MoS2@KHCO3 nanosheets and ultrapure water for 10 minutes at a speed of 250rpm; add the thickener and continue stirring for 40 minutes at a speed of 500rpm; add the adhesive and stir for 40 minutes at a speed of 600rpm; add the wetting agent and defoaming agent and stir for 30 minutes at a speed of 600rpm; filter and remove iron to obtain a coating slurry;
[0047] In terms of mass percentage, the raw material composition of the coating slurry is: 8.5% wrinkled MoS2@KHCO3 nanosheets, 0.6% dispersant, 20% PVDF powder, 7% thickener, 2% adhesive, 0.2% wetting agent, 0.05% defoamer, and the balance is ultrapure water;
[0048] The dispersant is an aliphatic amide dispersant, the thickener is sodium hydroxymethyl cellulose, the wetting agent is an alkyl sulfate wetting agent, the defoamer is a polyether defoamer, and the binder is polyacrylic acid;
[0049] S4: Using a micro-gravure roller coating process, the prepared coating slurry is step-by-step roller-coated on both sides of a 9μm polyolefin separator by a coater, with a single-side coating thickness of 3μm. It is baked at 65°C and rolled up to obtain a highly bonded lithium-ion battery separator.
[0050] Example 2
[0051] A method for preparing a highly bonded lithium-ion battery separator comprises the following steps:
[0052] S1: Preparation of wrinkled MoS2 nanosheets:
[0053] Sodium molybdate dihydrate and ultrapure water were mixed, ultrasonically treated for 9 minutes, L-cysteine was added and ultrasonically treated for 9 minutes to obtain a sodium molybdate mixed solution, which was transferred to a stainless steel autoclave with a PTFE liner and kept at 218°C for 23 hours; naturally cooled, centrifuged, and washed alternately with deionized water and anhydrous ethanol for 4 times; after drying, the obtained powder was mixed with hydrazine hydrate with a mass fraction of 80% at a mass volume ratio of 1g:20mL, transferred to a stainless steel autoclave with a PTFE liner, kept at 92°C for 4.5 hours, naturally cooled, filtered, and washed alternately with deionized water and anhydrous ethanol for 4 times, annealed to obtain wrinkled MoS2 nanosheets;
[0054] The composition of the sodium molybdate mixed solution is: ultrapure water as solvent, wherein dihydrate sodium molybdate is 0.06 mol / L, and L-cysteine is 0.46 mol / L; the working conditions of the annealing treatment are: annealing temperature is 800°C, and annealing time is 2h;
[0055] S2: Preparation of wrinkled MoS2@KHCO3 nanosheets using wrinkled MoS2 nanosheets:
[0056] 1.33 g of wrinkled MoS2 nanosheets and 100 mL of ultrapure water were mixed and stirred for 3.5 h, ultrasonically dispersed for 5.5 h, 115 g of potassium carbonate was added and stirred to dissolve, and then a mixture of carbon dioxide and nitrogen was introduced for 150-170 min, filtered, washed, and dried in a vacuum at 75 ° C for 23 h to obtain wrinkled MoS2@KHCO3 nanosheets;
[0057] The volume ratio of carbon dioxide to nitrogen in the mixed gas is 67.5:32.5, and the vacuum degree of vacuum drying is 0.08Mpa;
[0058] S3: Mix the dispersant, PVDF powder, wrinkled MoS2@KHCO3 nanosheets and ultrapure water for 20 minutes at a speed of 220 rpm; add the thickener and continue stirring for 45 minutes at a speed of 450 rpm; add the adhesive and stir for 50 minutes at a speed of 550 rpm; add the wetting agent and defoaming agent and stir for 40 minutes at a speed of 580 rpm; filter and remove iron to obtain a coating slurry;
[0059] In terms of mass percentage, the raw material composition of the coating slurry is: 13.5% wrinkled MoS2@KHCO3 nanosheets, 1.33% dispersant, 24.5% PVDF powder, 8.75% thickener, 3.3% adhesive, 0.37% wetting agent, 0.15% defoamer, and the balance is ultrapure water;
[0060] The dispersant is an aliphatic amide dispersant, the thickener is sodium hydroxymethyl cellulose, the wetting agent is an alkyl sulfate wetting agent, the defoamer is a polyether defoamer, and the binder is polyacrylic acid;
[0061] S4: Using a micro-gravure roller coating process, the prepared coating slurry is step-by-step roller-coated on both sides of a 9μm polyolefin separator by a coater, with a single-side coating thickness of 3μm. The film is baked at 70°C and rolled up to obtain a highly bonded lithium-ion battery separator.
[0062] Example 3
[0063] A method for preparing a highly bonded lithium-ion battery separator comprises the following steps:
[0064] S1: Preparation of wrinkled MoS2 nanosheets:
[0065] Sodium molybdate dihydrate and ultrapure water were mixed, ultrasonically treated for 10 minutes, L-cysteine was added and ultrasonically treated for 10 minutes to obtain a sodium molybdate mixed solution, which was transferred to a stainless steel autoclave with a PTFE liner and kept at 220°C for 22 hours; naturally cooled, centrifuged, and washed alternately with deionized water and anhydrous ethanol for 5 times; after drying, the obtained powder was mixed with hydrazine hydrate with a mass fraction of 80% at a mass volume ratio of 1g:20mL, transferred to a stainless steel autoclave with a PTFE liner, kept at 95°C for 4 hours, naturally cooled, filtered, and washed alternately with deionized water and anhydrous ethanol for 5 times, annealed to obtain wrinkled MoS2 nanosheets;
[0066] The composition of the sodium molybdate mixed solution is: ultrapure water as solvent, wherein dihydrate sodium molybdate is 0.06 mol / L, and L-cysteine is 0.46 mol / L; the working conditions of the annealing treatment are: annealing temperature is 800°C, and annealing time is 2h;
[0067] S2: Preparation of wrinkled MoS2@KHCO3 nanosheets using wrinkled MoS2 nanosheets:
[0068] 1.33 g of wrinkled MoS2 nanosheets and 100 mL of ultrapure water were mixed and stirred for 4 h, ultrasonically dispersed for 6 h, 115 g of potassium carbonate was added and stirred to dissolve, and then a mixed gas of carbon dioxide and nitrogen was introduced for 170 min, filtered, washed, and placed in a vacuum dryer at 80 ° C for 22 h to obtain wrinkled MoS2@KHCO3 nanosheets;
[0069] The volume ratio of carbon dioxide to nitrogen in the mixed gas is 67.5:32.5, and the vacuum degree of vacuum drying is 0.08Mpa;
[0070] S3: Mix the dispersant, PVDF powder, wrinkled MoS2@KHCO3 nanosheets and ultrapure water for 30 minutes at a speed of 200 rpm; add the thickener and continue stirring for 50 minutes at a speed of 400 rpm; add the adhesive and stir for 60 minutes at a speed of 500 rpm; add the wetting agent and defoaming agent and stir for 50 minutes at a speed of 550 rpm; filter and remove iron to obtain a coating slurry;
[0071] In terms of mass percentage, the raw material composition of the coating slurry is: 18.5% wrinkled MoS2@KHCO3 nanosheets, 1.6% dispersant, 25% PVDF powder, 10% thickener, 4% adhesive, 0.5% wetting agent, 0.2% defoamer, and the balance is ultrapure water;
[0072] The dispersant is an aliphatic amide dispersant, the thickener is sodium hydroxymethyl cellulose, the wetting agent is an alkyl sulfate wetting agent, the defoamer is a polyether defoamer, and the binder is polyacrylic acid;
[0073] S4: Using a micro-gravure roller coating process, the prepared coating slurry is step-by-step roller-coated on both sides of a 9μm polyolefin separator by a coater, with a single-side coating thickness of 3μm. It is baked at 75°C and rolled up to obtain a highly bonded lithium-ion battery separator.
[0074] Example 4
[0075] A method for preparing a highly bonded lithium-ion battery separator comprises the following steps:
[0076] S1: Preparation of wrinkled MoS2 nanosheets:
[0077] Sodium molybdate dihydrate and ultrapure water were mixed, ultrasonically treated for 8 minutes, L-cysteine was added and ultrasonically treated for 8 minutes to obtain a sodium molybdate mixed solution, which was transferred to a stainless steel autoclave with a PTFE liner and kept at 215°C for 24 hours; naturally cooled, centrifuged, and washed alternately with deionized water and anhydrous ethanol for 3 times; after drying, the obtained powder was mixed with hydrazine hydrate with a mass fraction of 80% at a mass volume ratio of 1g:20mL, transferred to a stainless steel autoclave with a PTFE liner, kept at 90°C for 5 hours, naturally cooled, filtered, and washed alternately with deionized water and anhydrous ethanol for 3 times, annealed to obtain wrinkled MoS2 nanosheets;
[0078] The composition of the sodium molybdate mixed solution is: ultrapure water as solvent, wherein dihydrate sodium molybdate is 0.06 mol / L, and L-cysteine is 0.46 mol / L; the working conditions of the annealing treatment are: annealing temperature is 800°C, and annealing time is 2h;
[0079] S2: Preparation of wrinkled MoS2@KHCO3 nanosheets using wrinkled MoS2 nanosheets:
[0080] 1.33 g of wrinkled MoS2 nanosheets and 100 mL of ultrapure water were mixed and stirred for 3 h, ultrasonically dispersed for 5 h, 115 g of potassium carbonate was added and stirred to dissolve, and then a mixed gas of carbon dioxide and nitrogen was introduced for 150 min, filtered, washed, and placed in a vacuum dryer at 70 ° C for 24 h to obtain wrinkled MoS2@KHCO3 nanosheets;
[0081] The volume ratio of carbon dioxide to nitrogen in the mixed gas is 67.5:32.5, and the vacuum degree of vacuum drying is 0.08Mpa;
[0082] S3: Mix PVDF powder, wrinkled MoS2@KHCO3 nanosheets and ultrapure water for 10 minutes at a speed of 250rpm; add thickener and continue stirring for 40 minutes at a speed of 500rpm; add adhesive and stir for 40 minutes at a speed of 600rpm; add wetting agent and defoaming agent and stir for 30 minutes at a speed of 600rpm; filter and remove iron to obtain coating slurry;
[0083] In terms of mass percentage, the raw material composition of the coating slurry is: 8.5% wrinkled MoS2@KHCO3 nanosheets, 20% PVDF powder, 7% thickener, 2% adhesive, 0.2% wetting agent, 0.05% defoamer, and the balance is ultrapure water;
[0084] The thickener is sodium hydroxymethyl cellulose, the wetting agent is an alkyl sulfate wetting agent, and the defoaming agent is a polyether defoaming agent;
[0085] The binder is modified polyethyleneimine, and the preparation comprises the following steps:
[0086] 1 mL of branched polyethyleneimine and 1 mL of 0.5 wt.% NaOH solution were mixed and stirred, 100 μL of epichlorohydrin was added, and the mixture was kept warm at 3°C for 15 min; 0.567 g of β-cyclodextrin and 1 mL of ultrapure water were added, and the mixture was kept warm in a 55°C water bath for 2 h; 0.02 g of terephthalaldehyde and 1 mL of methanol were added, and the mixture was stirred for 40 min; 0.025 g of p-formylbenzoic acid was added, and the mixture was stirred for 20 min; the mixture was dried under vacuum at 50°C for 12 h to obtain modified polyethyleneimine;
[0087] The PVDF powder is a modified PVDF powder, and the preparation thereof comprises the following steps:
[0088] 1) Wash the ion exchange resin with deionized water until it is neutral, and then put it into a chromatography column; dilute the [EMIM]Br concentration to 0.05 mol / L with deionized water, put it into the chromatography column and let it stand for 1 hour, dripping at a speed of 50 s / drop. After the exchange is complete, neutralize it with 3-mercaptopropionic acid to a pH of 5.4, and rotary evaporate to obtain an ionic liquid;
[0089] 2) 1 mmol 1H-pyrrole-2,5-dicarboxylic acid, 2 mmol sodium hydroxide and 5 mL water were mixed, ultrasonically stirred, 1 mmol aluminum chloride hexahydrate was added, stirred for 20 min, heated to 100 ° C and stirred for 11 h, filtered and washed with water and ethanol three times in sequence to obtain an aluminum-based organic framework;
[0090] 3) 5 mg of lithium bis(trifluoromethanesulfonyl)imide and 1 mg of ionic liquid were mixed and stirred, and the mixture was kept at 90° C. for 12 h. 5 mg of aluminum-based organic framework was added and ground, and then vacuum-insulated at 90° C. for 12 h to obtain modified lithium ion powder; 5 mg of modified lithium ion powder and 30 mL of N,N-dimethylformamide were mixed and stirred, 50 mg of PVDF powder was added and continued to be stirred, and the mixture was dried and ground to obtain modified PVDF powder;
[0091] S4: Using a micro-gravure roller coating process, the prepared coating slurry is step-by-step roller-coated on both sides of a 9μm polyolefin separator by a coater, with a single-side coating thickness of 3μm. It is baked at 65°C and rolled up to obtain a highly bonded lithium-ion battery separator.
[0092] Example 5
[0093] A method for preparing a highly bonded lithium-ion battery separator comprises the following steps:
[0094] S1: Preparation of wrinkled MoS2 nanosheets:
[0095] Sodium molybdate dihydrate and ultrapure water were mixed, ultrasonically treated for 9 minutes, L-cysteine was added and ultrasonically treated for 9 minutes to obtain a sodium molybdate mixed solution, which was transferred to a stainless steel autoclave with a PTFE liner and kept at 218°C for 23 hours; naturally cooled, centrifuged, and washed alternately with deionized water and anhydrous ethanol for 4 times; after drying, the obtained powder was mixed with hydrazine hydrate with a mass fraction of 80% at a mass volume ratio of 1g:20mL, transferred to a stainless steel autoclave with a PTFE liner, kept at 92°C for 4.5 hours, naturally cooled, filtered, and washed alternately with deionized water and anhydrous ethanol for 4 times, annealed to obtain wrinkled MoS2 nanosheets;
[0096] The composition of the sodium molybdate mixed solution is: ultrapure water as solvent, wherein dihydrate sodium molybdate is 0.06 mol / L, and L-cysteine is 0.46 mol / L; the working conditions of the annealing treatment are: annealing temperature is 800°C, and annealing time is 2h;
[0097] S2: Preparation of wrinkled MoS2@KHCO3 nanosheets using wrinkled MoS2 nanosheets:
[0098] 1.33 g of wrinkled MoS2 nanosheets and 100 mL of ultrapure water were mixed and stirred for 3.5 h, ultrasonically dispersed for 5.5 h, 115 g of potassium carbonate was added and stirred to dissolve, and then a mixture of carbon dioxide and nitrogen was introduced for 160 min, filtered, washed, and placed in a vacuum dryer at 75 ° C for 23 h to obtain wrinkled MoS2@KHCO3 nanosheets;
[0099] The volume ratio of carbon dioxide to nitrogen in the mixed gas is 67.5:32.5, and the vacuum degree of vacuum drying is 0.08Mpa;
[0100] S3: Mix PVDF powder, wrinkled MoS2@KHCO3 nanosheets and ultrapure water for 20 minutes at a speed of 220 rpm; add thickener and continue stirring for 45 minutes at a speed of 450 rpm; add adhesive and stir for 50 minutes at a speed of 550 rpm; add wetting agent and defoaming agent and stir for 40 minutes at a speed of 580 rpm; filter and remove iron to obtain coating slurry;
[0101] In terms of mass percentage, the raw material composition of the coating slurry is: 13.5% wrinkled MoS2@KHCO3 nanosheets, 24.5% PVDF powder, 8.75% thickener, 3.3% adhesive, 0.37% wetting agent, 0.15% defoamer, and the balance is ultrapure water;
[0102] The thickener is sodium hydroxymethyl cellulose, the wetting agent is an alkyl sulfate wetting agent, and the defoaming agent is a polyether defoaming agent;
[0103] The binder is modified polyethyleneimine, and the preparation comprises the following steps:
[0104] 1 mL of branched polyethyleneimine and 1 mL of 0.5 wt.% NaOH solution were mixed and stirred, 100 μL of epichlorohydrin was added, and the mixture was kept warm at 3°C for 18 min; 0.567 g of β-cyclodextrin and 1 mL of ultrapure water were added, and the mixture was kept warm in a 58°C water bath for 2 h; 0.02 g of terephthalaldehyde and 1 mL of methanol were added, and the mixture was stirred for 50 min; 0.025 g of p-formylbenzoic acid was added, and the mixture was stirred for 25 min; the mixture was dried under vacuum at 55°C for 11.5 h to obtain modified polyethyleneimine;
[0105] The PVDF powder is a modified PVDF powder, and the preparation thereof comprises the following steps:
[0106] 1) Wash the ion exchange resin with deionized water until it is neutral, and then put it into a chromatography column; dilute the [EMIM]Br concentration to 0.05 mol / L with deionized water, put it into the chromatography column and let it stand for 1.5 hours, dripping at a rate of 50 seconds per drop. After the exchange is complete, neutralize it with 3-mercaptopropionic acid to a pH of 5.4, and rotary evaporate to obtain an ionic liquid;
[0107] 2) 1 mmol 1H-pyrrole-2,5-dicarboxylic acid, 2 mmol sodium hydroxide and 5 mL water were mixed, ultrasonically stirred, 1 mmol aluminum chloride hexahydrate was added, stirred for 25 min, heated to 100 ° C and stirred for 11.5 h, filtered and washed with water and ethanol 4 times in sequence to obtain an aluminum-based organic framework;
[0108] 3) 5 mg of lithium bis(trifluoromethanesulfonyl)imide and 1 mg of ionic liquid were mixed and stirred, and the mixture was kept at 95° C. for 11.5 h. 5 mg of aluminum-based organic framework was added and ground, and then vacuum-insulated at 95° C. for 11.5 h to obtain modified lithium ion powder; 8 mg of modified lithium ion powder and 30 mL of N,N-dimethylformamide were mixed and stirred, 50 mg of PVDF powder was added and continued to be stirred, and the mixture was dried and ground to obtain modified PVDF powder;
[0109] S4: Using a micro-gravure roller coating process, the prepared coating slurry is step-by-step roller-coated on both sides of a 9μm polyolefin separator by a coater, with a single-side coating thickness of 3μm. The film is baked at 70°C and rolled up to obtain a highly bonded lithium-ion battery separator.
[0110] Example 6
[0111] A method for preparing a highly bonded lithium-ion battery separator comprises the following steps:
[0112] S1: Preparation of wrinkled MoS2 nanosheets:
[0113] Sodium molybdate dihydrate and ultrapure water were mixed, ultrasonically treated for 10 minutes, L-cysteine was added and ultrasonically treated for 10 minutes to obtain a sodium molybdate mixed solution, which was transferred to a stainless steel autoclave with a PTFE liner and kept at 220°C for 22 hours; naturally cooled, centrifuged, and washed alternately with deionized water and anhydrous ethanol for 5 times; after drying, the obtained powder was mixed with hydrazine hydrate with a mass fraction of 80% at a mass volume ratio of 1g:20mL, transferred to a stainless steel autoclave with a PTFE liner, kept at 95°C for 4 hours, naturally cooled, filtered, and washed alternately with deionized water and anhydrous ethanol for 5 times, annealed to obtain wrinkled MoS2 nanosheets;
[0114] The composition of the sodium molybdate mixed solution is: ultrapure water as solvent, wherein dihydrate sodium molybdate is 0.06 mol / L, and L-cysteine is 0.46 mol / L; the working conditions of the annealing treatment are: annealing temperature is 800°C, and annealing time is 2h;
[0115] S2: Preparation of wrinkled MoS2@KHCO3 nanosheets using wrinkled MoS2 nanosheets:
[0116] 1.33 g of wrinkled MoS2 nanosheets and 100 mL of ultrapure water were mixed and stirred for 4 h, ultrasonically dispersed for 6 h, 115 g of potassium carbonate was added and stirred to dissolve, and then a mixed gas of carbon dioxide and nitrogen was introduced for 170 min, filtered, washed, and placed in a vacuum dryer at 80 ° C for 22 h to obtain wrinkled MoS2@KHCO3 nanosheets;
[0117] The volume ratio of carbon dioxide to nitrogen in the mixed gas is 67.5:32.5, and the vacuum degree of vacuum drying is 0.08Mpa;
[0118] S3: Mix PVDF powder, wrinkled MoS2@KHCO3 nanosheets and ultrapure water for 30 minutes at a speed of 200 rpm; add thickener and continue stirring for 50 minutes at a speed of 400 rpm; add adhesive and stir for 60 minutes at a speed of 500 rpm; add wetting agent and defoaming agent and stir for 50 minutes at a speed of 550 rpm; filter and remove iron to obtain coating slurry;
[0119] In terms of mass percentage, the raw material composition of the coating slurry is: 18.5% wrinkled MoS2@KHCO3 nanosheets, 25% PVDF powder, 10% thickener, 4% adhesive, 0.5% wetting agent, 0.2% defoamer, and the balance is ultrapure water;
[0120] The thickener is sodium hydroxymethyl cellulose, the wetting agent is an alkyl sulfate wetting agent, and the defoaming agent is a polyether defoaming agent;
[0121] The binder is modified polyethyleneimine, and the preparation comprises the following steps:
[0122] 1 mL of branched polyethyleneimine and 1 mL of 0.5 wt.% NaOH solution were mixed and stirred, 100 μL of epichlorohydrin was added, and the mixture was kept warm at 4°C for 20 min; 0.567 g of β-cyclodextrin and 1 mL of ultrapure water were added, and the mixture was kept warm in a water bath at 60°C for 2 h; 0.02 g of terephthalaldehyde and methanol were added, and the mixture was stirred for 60 min; 0.025 g of p-formylbenzoic acid was added, and the mixture was stirred for 30 min; the mixture was dried under vacuum at 60°C for 11 h to obtain modified polyethyleneimine;
[0123] The PVDF powder is a modified PVDF powder, and the preparation thereof comprises the following steps:
[0124] 1) Wash the ion exchange resin with deionized water until it is neutral, and then put it into a chromatography column; dilute the [EMIM]Br concentration to 0.05 mol / L with deionized water, put it into the chromatography column and let it stand for 2 hours, dripping at a speed of 50 seconds per drop. After the exchange is complete, neutralize it with 3-mercaptopropionic acid to a pH of 5.4, and rotary evaporate to obtain an ionic liquid;
[0125] 2) 1 mmol 1H-pyrrole-2,5-dicarboxylic acid, 2 mmol sodium hydroxide and 5 mL water were mixed, ultrasonically stirred, 1 mmol aluminum chloride hexahydrate was added, stirred for 30 min, heated to 100 ° C and stirred for 12 h, filtered and washed with water and ethanol for 5 times in sequence to obtain an aluminum-based organic framework;
[0126] 3) 5 mg of lithium bis(trifluoromethanesulfonyl)imide and 1 mg of ionic liquid were mixed and stirred, and the mixture was kept at 100° C. for 11 h. 5 mg of aluminum-based organic framework was added and ground, and then vacuum-insulated at 100° C. for 11 h to obtain modified lithium ion powder; 10 mg of modified lithium ion powder and 30 mL of N,N-dimethylformamide were mixed and stirred, 50 mg of PVDF powder was added and continued to be stirred, and the mixture was dried and ground to obtain modified PVDF powder;
[0127] S4: Using a micro-gravure roller coating process, the prepared coating slurry is step-by-step roller-coated on both sides of a 9μm polyolefin separator by a coater, with a single-side coating thickness of 3μm. It is baked at 75°C and rolled up to obtain a highly bonded lithium-ion battery separator.
[0128] Comparative Example 1
[0129] Example 3 was used as the control group, in which wrinkled MoS2@KHCO3 nanosheets were not prepared, and other processes were normal.
[0130] Comparative Example 2
[0131] Example 6 was used as a control group, in which branched polyethyleneimine was used to replace modified polyethyleneimine, and other processes were normal.
[0132] Comparative Example 3
[0133] Example 6 was used as a control group, in which the modified PVDF powder was replaced by PVDF powder, and the other processes were normal.
[0134] Comparative Example 4
[0135] Taking Example 6 as the control group, when preparing the modified PVDF powder, no aluminum-based organic framework was prepared, and other processes were normal.
[0136] Comparative Example 5
[0137] Taking Example 6 as the control group, when preparing the modified PVDF powder, no ionic liquid was prepared, and other processes were normal.
[0138] Comparative Example 6
[0139] Example 6 was used as a control group, in which no coating was applied and other processes were normal.
[0140] The polyolefin membranes used in Examples 1-6 and Comparative Examples 1-6 are all polyethylene membranes.
[0141] The sources of raw materials used in the above examples and comparative examples are:
[0142] Sodium molybdate dihydrate S817613, L-cysteine L804954, aluminum chloride hexahydrate A801040, lithium bis(trifluoromethanesulfonyl)imide B802083, aliphatic amide A875185: Shanghai McLean Biochemical Technology Co., Ltd.; PVDF powder (MZ=197nm): Dongguan Yingde Plastic Co., Ltd.; epichlorohydrin 492515, hydrazine hydrate 53847, sodium hydroxymethyl cellulose 419273, polyacrylic acid 181285, alkyl sulfate wetting agent is sodium dodecyl sulfate RDD021, polyether defoaming agent is polymer of methyl oxirane, 1,2-ethylenediamine and ethylene oxide 435546: Merck reagent; β-cyclodextrin, branched poly Ethylenimine (Mw=800, Mn=600): Sigma-Aldrich Company; terephthalaldehyde (AR), p-formylbenzoic acid (AR): San Chemical Technology (Shanghai) Co., Ltd.; 3-Mercaptopropionic acid (98%), alkaline ion exchange resin (900): Shanghai Aladdin Biochemical Technology Co., Ltd.; [EMIM]Br (1-ethyltrimethylimidazolium bromide, mass fraction >99%): Lanzhou Chemical Industry Company; 1H-pyrrole-2,5-dicarboxylic acid: Shanghai Bid Pharmaceutical Technology Co., Ltd.; potassium carbonate, anhydrous ethanol, methanol, sodium hydroxide, N,N-dimethylformamide: Sinopharm Chemical Reagent Co., Ltd.; polyethylene diaphragm: Guangzhou Rongdong Chemical Co., Ltd.
[0143] Performance Testing:
[0144] The battery separators prepared in Examples 1-6 and Comparative Examples 1-6 were subjected to performance tests;
[0145] Refer to GB / T36363-2018 to test thickness, air permeability, needle puncture strength and thermal shrinkage;
[0146] Peel strength: Sample size 100mm×15mm, tested using a tensile testing machine;
[0147] Liquid absorption rate determination: The sample size is 50mm×50mm. After drying the sample for 24 hours, take it out and weigh the sample, which is recorded as M. Immerse the sample in a beaker filled with electrolyte, keep it for 10 minutes, then take it out and weigh it immediately, which is recorded as M1. Liquid absorption rate = (M1-M) / M, (accurate to 0.01g);
[0148] Anode-hot pressing peeling: Dry the anode electrode sheet of lithium battery with a size of 6×11cm, cut the test sample into 8×13cm, place it under the anode electrode sheet, cover it with A4 paper on both sides, transfer it to the middle of the upper and lower hot pressing plates of the hot press for 2 minutes, the pressure is 4MPa, the temperature of the hot pressing plate is 92℃, preheat for 15s, take it out after completion, and perform peel strength test on it;
[0149] Oxygen index: Tested with reference to IOS4589-2, oxygen and nitrogen mixed gas flowing upward in laminar flow is introduced into a transparent combustion tube, and the sample is placed in it. The temperature of the mixed gas is 25°C; when the top surface is ignited, the flame contacts the top surface for 25 seconds, and is removed every 5 seconds to observe whether the diaphragm is burning. The minimum oxygen concentration required to maintain combustion is the oxygen index; the results are shown in Table 1;
[0150]
[0151]
[0152] Table 1
[0153] The present invention provides a high-adhesion lithium-ion battery separator and a preparation method thereof. PVDF powder and wrinkled MoS2@KHCO3 nanosheets are selected to prepare the separator. The obtained lithium-ion battery separator has high flame retardancy, high adhesion and good electrophilic electrolyte performance.
[0154] By comparing Examples 1-3, Comparative Example 1, and Comparative Example 6, it can be seen that the MoS2@KHCO3 nanosheets greatly improve the mechanical strength (needle puncture strength) of the diaphragm; when the mass ratio of the wrinkled MoS2@KHCO3 nanosheets in the slurry is gradually increased, the anode-hot pressing stripping performance, heat shrinkage performance, and flame retardancy of the corresponding composite diaphragm are getting better and better, and are all higher than the composite diaphragm corresponding to the slurry without adding wrinkled MoS2@KHCO3 nanosheets, and are much higher than the pure polyolefin diaphragm without coating; the coating peeling strength of the corresponding composite diaphragm is getting higher and higher, that is, the anti-powdering ability is getting stronger and stronger, and is much higher than the composite diaphragm corresponding to the slurry without adding wrinkled MoS2@KHCO3 nanosheets, which confirms the effectiveness of the wrinkled MoS2@KHCO3 nanosheets in preventing powdering;
[0155] When the mass ratio of wrinkled MoS2@KHCO3 nanosheets in the slurry gradually increases, the air permeability of the corresponding composite membrane becomes worse. When the mass ratio of wrinkled MoS2@KHCO3 nanosheets further increases, the air permeability of the corresponding composite membrane seriously deteriorates, and is worse than the composite membrane corresponding to the slurry without wrinkled MoS2@KHCO3 nanosheets and the pure polyolefin membrane without coating. Therefore, in order to balance the various performances of the composite membrane, the addition amount of wrinkled MoS2@KHCO3 nanosheets should be moderate, not the more the better.
[0156] Comparing Example 6 with Comparative Example 2, the present invention adopts modified polyethyleneimine as a binder to increase the ion loading capacity of the diaphragm; first, β-dextrin is chemically cross-linked with branched polyethyleneimine to form a prepolymer, and then terephthalaldehyde and p-formylbenzoic acid are used to continue cross-linking to prepare a self-healing binder with a network structure, and the self-healing property of the binder is used to improve the stability of the microstructure of the diaphragm, and the reversible destruction and formation of chemical bonds are used to repair the structural damage caused by the volume change of the diaphragm, and to enhance the mechanical strength of the diaphragm, thereby facilitating the improvement of the battery's specific capacity and cycle stability and other characteristics; the carboxyl group in the self-healing binder can combine with lithium ions, provide a migration path for lithium ions, and greatly enhance the ion exchange capacity of the diaphragm.
[0157] Example 6 is compared with Comparative Example 3. In order to make the adhesion of PVDF powder to MoS2@KHCO3 nanosheets durable, the present invention modifies the PVDF powder so that the PVDF powder adheres evenly and firmly to the MoS2@KHCO3 nanosheets, and the addition of modified PVDF powder greatly improves the ionic conductivity and flame retardancy of the diaphragm.
[0158] Example 6 is compared with Comparative Example 4 and Comparative Example 5. A functionalized lithium ion liquid containing a thiol group and an aluminum-based organic framework are first prepared. An aluminum-based organic framework material with a three-dimensional structure having a high stability is synthesized by a simple and green hydrothermal method. The high porosity and high adsorption of the aluminum-based organic framework are used to enclose the lithium ion liquid to form an ion conductor. The adsorption of the lithium ion liquid will not affect the performance of the aluminum-based organic framework, thereby modifying the PVDF powder to synergistically improve the ionic conductivity, flame retardancy and high temperature resistance of the diaphragm.
[0159] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A highly bonded lithium-ion battery separator, characterized in that: It includes a base film and a coating layer, wherein the raw materials in the coating layer are composed of 8.5%-18.5% wrinkled MoS2@KHCO3 nanosheets, 0-1.6% dispersant, 20%-25% PVDF powder, 7%-10% thickener, 2%-4% binder, 0.2%-0.5% wetting agent, 0.05%-0.2% defoamer, and the balance is ultrapure water; The binder is modified polyethyleneimine, and the preparation comprises the following steps: The branched polyethyleneimine and NaOH solution are mixed and stirred, epichlorohydrin is added, and the mixture is kept warm at 3-4°C for 15-20 minutes; β-cyclodextrin and ultrapure water are added, and the mixture is kept warm at 55-60°C for 2 hours in a water bath, terephthalaldehyde and methanol are added, and the mixture is stirred for 40-60 minutes, p-formylbenzoic acid is added, and the mixture is stirred for 20-30 minutes, and the mixture is vacuum dried at 50-60°C for 11-12 hours to obtain modified polyethyleneimine; The PVDF powder is a modified PVDF powder, and the preparation thereof comprises the following steps: 1) Wash the ion exchange resin with deionized water until it is neutral, and then put it into the chromatography column; dilute the [EMIM]Br concentration to 0.05 mol / L with deionized water, put it into the chromatography column and let it stand for 1-2 hours, dripping at a rate of 50 seconds per drop. After the exchange is complete, neutralize it with 3-mercaptopropionic acid to a pH of 5.4, and rotary evaporate to obtain an ionic liquid; 2) 1H-pyrrole-2,5-dicarboxylic acid, sodium hydroxide and ultrapure water are mixed, ultrasonically stirred, aluminum chloride hexahydrate is added, stirred for 20-30 minutes, heated to 100°C and stirred for 11-12 hours, filtered and washed with water and ethanol for 3-5 times in sequence to obtain an aluminum-based organic framework; 3) Lithium bis(trifluoromethanesulfonyl)imide and ionic liquid are mixed and stirred, kept at 90-100°C for 11-12 hours, an aluminum-based organic framework is added and ground, and then vacuum dried at 90-100°C for 11-12 hours to obtain modified lithium ion powder; the modified lithium ion powder and N,N-dimethylformamide are mixed and stirred, PVDF powder is added and continued to be stirred, and the modified PVDF powder is ground after drying to obtain modified PVDF powder.
2. A highly adhesive lithium-ion battery separator according to claim 1, characterized in that: The preparation of the wrinkled MoS2@KHCO3 nanosheets comprises the following steps: The wrinkled MoS2 nanosheets and ultrapure water were mixed and stirred for 3-4 hours, ultrasonically dispersed for 5-6 hours, potassium carbonate was added and stirred to dissolve, and then a mixed gas of carbon dioxide and nitrogen was introduced for 150-170 minutes, filtered and washed, and placed in a vacuum dryer at 70-80°C for 22-24 hours to obtain wrinkled MoS2@KHCO3 nanosheets.
3. A highly adhesive lithium-ion battery separator according to claim 2, characterized in that: The volume ratio of carbon dioxide to nitrogen in the mixed gas is 67.5:32.5, and the vacuum degree of vacuum drying is 0.08 MPa.
4. A highly adhesive lithium-ion battery separator according to claim 2, characterized in that: The preparation of wrinkled MoS2 nanosheets includes the following steps: Sodium molybdate dihydrate and ultrapure water are mixed, and ultrasonic treatment is performed for 8-10 minutes. L-cysteine is added and ultrasonic treatment is performed for 8-10 minutes to obtain a sodium molybdate mixed solution, which is then transferred to a stainless steel autoclave with a PTFE liner and kept at 215-220°C for 22-24 hours; the solution is naturally cooled, centrifuged, and washed alternately with deionized water and anhydrous ethanol for 3-5 times; after drying, the obtained powder is mixed with hydrazine hydrate at a mass volume ratio of 1g:20mL, and the solution is transferred to a stainless steel autoclave with a PTFE liner, and kept at 90-95°C for 4-5 hours; the solution is naturally cooled, filtered, and washed alternately with deionized water and anhydrous ethanol for 3-5 times; and annealed to obtain wrinkled MoS2 nanosheets.
5. A highly adhesive lithium-ion battery separator according to claim 4, characterized in that: The composition of the sodium molybdate mixed solution is: ultrapure water as solvent, wherein dihydrate sodium molybdate is 0.06 mol / L, and L-cysteine is 0.46 mol / L; the working conditions of the annealing treatment are: annealing temperature is 800° C., and annealing time is 2 h.
6. A highly adhesive lithium-ion battery separator according to claim 1, characterized in that: In the preparation of modified polyethyleneimine, the volume mass ratio of branched polyethyleneimine, epichlorohydrin, β-cyclodextrin, terephthalaldehyde, and p-formylbenzoic acid is 1 mL: 100 μL: 0.567 g: 0.02 g: 0.025 g.
7. A method for preparing a highly adhesive lithium-ion battery separator according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Preparation of wrinkled MoS2 nanosheets; S2: Preparation of wrinkled MoS2@KHCO3 nanosheets using wrinkled MoS2 nanosheets; S3: Mix the dispersant, PVDF powder, wrinkled MoS2@KHCO3 nanosheets and ultrapure water for 10-30 minutes at a speed of 200-250rpm; add the thickener and continue stirring for 40-50 minutes at a speed of 400-500rpm; add the binder and stir for 40-60 minutes at a speed of 500-600rpm; add the wetting agent and defoaming agent and stir for 30-50 minutes at a speed of 550-600rpm; filter and remove iron to obtain a coating slurry; S4: The prepared coating slurry is roll-coated on both sides of the polyolefin separator in steps by using a micro-gravure roller coating process, baked at 65-75°C, and rolled up to obtain a highly adhesive lithium-ion battery separator.
8. A highly adhesive lithium-ion battery separator according to claim 1, characterized in that: In the preparation of modified PVDF powder, the mass ratio of modified lithium ion powder to PVDF powder is 10%-20%.
Citation Information
Patent Citations
Powder-falling-prevention and high-adhesion PVDF glued diaphragm and preparation method thereof
CN114094276A
High-stability strong-ionic-conductivity aqueous polymer slurry for lithium battery diaphragm and preparation method of high-stability strong-ionic-conductivity aqueous polymer slurry
CN114525060A